PARADIGMA PENDIDIKAN ISLAM DALAM MASYARAKAT JAWA - Jupriyanto Jupriyanto (Al Hikmah: Jurnal Studi Keislaman, 2011)
Islamic Education in the Java community through multiple ways including the adaptation of the teachings of Islam with Javanese culture. The adaptation are: (1) adaptation in the field of Fiqh. Characteristics of the Java community is more steady and confident when any conduct of worship using the Arabic pronunciation coupled with the Java language, this is done by the Java community until now as a result of Islamic education in Java, for example by combining the teachings of fiqh in the Java language when reciting intention in taking a ritual ablution, "niat ingsun wudlu ngilangake hadas cilik perdu kerono Allah ta’ala" (I intend to take a ritual ablution to eliminate small hadast because of Allah Ta’ala). Fasting Ramadlon intentions, "niat ingsun poso anekani sedino sesuk fardu kerono Allah ta’ala" (I intend to carry out a Full Day of Fasting for Allah Ta'ala) (2) adaptation in the fieldof magic formula / pray, for the people of Java Charms or do to have mystical powers that can give strength to someone who pray for because it contained the meaning of the prayer requests to God who created what is in the order can expect it can be granted (3) adaptation in field that contains the praises of Islamic da'wah. Praise-praise in use in the propagation of Islam because it is easy to understand, is understood and more familiar to Java community. Praise sung by the Moslem scholar of Islam in Java provides a positive impact on the development of Islam.